Investigating the consequences of urban creep in Shahrekord - ghorbanali karimi dehkordi; rahmatollah monshizadeh; bijan rahmani (تحقیقات کاربردی علوم جغرافیایی)
The rapid expansion of cities and their uneven physical growth, so-called "urban creep", have corrupted the villages and their surrounding lands, causing irregular conversion of agricultural lands and degradation of environmental resources. This situation has also been widespread in Shahrekord, the capital of Chaharmahal and Bakhtiari province. The purpose of this descriptive-survey research is to determine the physical developments of rural settlements around Shahrekord with emphasis on urban sprwal. The statistical population is household heads of rural areas (15000 people). Using the Krejcie and Morgan table, 400 individuals were selected. The tool used is a researcher-made questionnaire on three dimensions of economic, social, cultural and environmental physical consequences. Data were analyzed using one-sample t-test and Friedman test. The results show that the consequences of urban sprawl are respectively environmental-physical consequences (3/98), economic consequences (3/96) and socio-cultural consequences (3/89 (. The most important environmental-physical consequences are increased environmental pollution, destruction of traditional architecture, destruction of biodiversity; major economic consequences of stock markets and rising land and housing prices, diminishing villagers' reluctance to productive activities (agriculture and livestock), capital flight from villages And their savings in the city and the rising cost of living amidst the socio-cultural consequences of luxury and the tendency to consume luxury goods, reduce solidarity and participation, crowding and crowding in cities, modeling of life and urbanization culture. have been.